(untitled) (e-Journal of Linguistics, 2023)
This study is based on the structure of Dalihan na tolu which is composed of verb + verb in lines 1 and 2, and adverb + verb in line 3. These structures made Toba Batak people defined it in two ways; headed by somba, elek, and manat or headed by marhula-hula, marboru, and mardongan tubu. This study analyzed the valency and arguments in dalihan na tolu to define its real ideology. The findings explained (1) the three lines of dalihan na tolu are headed by the words of marhula-hula, marboru, and mardongan tubu, (2) while the way of how to apply the ideology is reflected from the words of somba, elek, and manat. These findings defined the real ideology of Toba Batak in dalihan na tolu is to create and maintain relations; brothers to sisters and siblings in the way of somba (respected), elek (loved), and manat (maintain). Additionally, the way people of Toba Batak show the ideology reflected in dalihan na tolu defined the ideology as an ambivalent story that is half aligning with the real message of dalihan na tolu itself.